Container ocean shipping network design considering carbon tax and choice inertia of cargo owners. (1st February 2022) - Gao, Shiqing; Xin, Xu; Li, Cui; Liu, Yanran; Chen, Kang
Abstract: The quality of the container ocean shipping network design directly affects the revenue of liner companies. In this paper, a container ocean shipping network design problem (COND) is investigated. Considering that the governments of many countries have proposed carbon-neutral initiatives, coupled with the constant fluctuations in the shipping market, the carbon tax and cargo owners' choice inertia factors are taken into consideration simultaneously. To model the COND, a bi-level programming model is developed to jointly optimize the liner type, calling sequence, calling frequency, and sailing speed. The upper model aims to choose the network design scheme that maximizes the liner company's revenue. The lower model optimizes the freight scheme of the liner company to evaluate the network design scheme selected by the upper model. To solve the abovementioned model, a genetic algorithm is designed, and a real-world trade shipping route between Asia and Western Europe is introduced to perform numerical experiments. Sensitivity analyses are conducted for different carbon tax rates and transportation demands. The experimental results show that the abovementioned model and algorithm can effectively address the COND and provide certain useful managerial insights for the liner company's daily operation. Graphical abstract: Image 1 Highlights: A liner shipping network design problem is investigated. The carbon tax and choice inertia of cargo owners are jointly considered. A bi-level programming model is established. A genetic algorithm is designed to solve the abovementioned model. The conclusions provide guidance to liner companies' daily operations.